ПОСЛОВИЦЫ И ПОГОВОРКИ КАК СРЕДСТВО ОТРАЖЕНИЯ КУЛЬТУРЫ НАРОДА - Рзаева, Р.К.; Ешимбетова, Н.; Жиенбаева, А. (SCIENCE and SOCIETY, 2018)
The article deals with the issues of intercultural communication in teaching English. There have been analyzed the sociocultural aspects of proverbs and sayings as a means of reflecting the culture of people. On the basis of the comparative analysis of proverbs and sayings in different languages the author of the article emphasizes the fact that foreign languages should be taught in connection with the world and culture of the people speaking in these languages.